The Role Played by Celebrities in the Promotion of Goods and Services in Cameroon (British Journal of Multidisciplinary and Advanced Studies, 2024)
Advertisers in Cameroon at the local and national level always make use of celebrities in their adverts so as to win the hearts of their potential customers. This form of promoting goods and services is visible on television and radio especially during some special programs organised by some radio and television houses such as ‘‘Equinoxe Soir’’ (Equinox Evening). Furthermore, most streets in Cameroon are coloured with billboard posters carrying the images of Cameroonian celebrities from the music, football and the entertainment industry advertising the products or services of companies such as MTN and Orange Cameroon just to name but these. This paper looks at types of celebrities used by marketers in Cameroon in the promotion of their goods or services, why Cameroonians use celebrities in their adverts and the advantages of using them in the promotion of their goods. The paper further explores the role they play in the promotion of goods and services on billboard posters. This study was conducted by using descriptive qualitative method. Random sampling technique was used to collect the sample of data from billboards posters (2022-2023). Furthermore, data was also culled from some television programs such as Equinox Evening. Source credibility theory was used to analyse the collected data. The analysis reveals that three types of celebrities are used by Cameroonians in their adverts. These celebrities are from the music, football and the entertainment industries. In addition, Cameroonians use celebrities in their adverts to attract the attention of the target audience as well as influence customers’ views of a product. The advantages of using celebrities by Cameroonians in their adverts is that it positions the brand in the minds of the target audience. More so, it attracts new users as well as breathe life into a failing brand. These celebrities play an enormous role in the marketing of goods and services in that, they invite the public to join them consume the goods or services they are seen promoting. This gesture makes the messages on these adverts to be credible. The credibility of these messages also makes the public to believe in what they say; thus an increase in sales.